Activity of Imipenem-Relebactam against a Large Collection of Pseudomonas aeruginosa Clinical Isolates and Isogenic β-Lactam-Resistant Mutants - Fraile-Ribot, Pablo A. (Antimicrob Agents Chemother, 2020)
Imipenem and imipenem-relebactam MICs were determined for 1,445 Pseudomonas aeruginosa clinical isolates and a large panel of isogenic mutants showing the most relevant mutation-driven β-lactam resistance mechanisms. Imipenem-relebactam showed the highest susceptibility rate (97.3%), followed by colistin and ceftolozane-tazobactam (both 94.6%). Imipenem-relebactam MICs remained ≤2 μg/ml in all 16 isogenic PAO1 mutants and in 8 pairs of extensively drug-resistant clinical strains that had developed resistance to ceftolozane-tazobactam and ceftazidime-avibactam due to mutations in OXA-10 or AmpC.